Competing Pathways in the Photogeneration of Didehydrotoluenes from (Trimethylsilylmethyl)aryl Sulfonates and Phosphates. Issue 52 (30th October 2014) - Crespi, Stefano; Ravelli, Davide; Protti, Stefano; Albini, Angelo; Fagnoni, Maurizio
Abstract The scope of the photochemical generation of α, n‐didehydrotoluene diradicals from aryl sulfonates and phosphates and their chemistry are explored. The thermally inaccessible α, 2‐ and α, 4‐ intermediates are efficiently obtained by irradiation of ortho‐ and para‐(trimethylsilylmethyl)phenyl triflates through heterolytic splitting of the ester anion from the substrate in the triplet state. Triplet phenyl cations are formed and the loss of trimethylsilyl cation from them affords the desired diradicals (3Me3SiCH2C6H4‐OZ→3Me3SiCH2C6H4+→⋅CH2C6H4⋅). Triplet sensitization is required, for which acetone is used throughout. Direct irradiation leads, on the contrary, to photo‐Fries fragmentation (1Me3SiCH2C6H4O‐Z→Me3SiCH2C6H4O⋅+Z⋅). With mesylates, where ester cleavage is less convenient, a further competition from the triplet is direct desilylation. Didehydrotoluenes are also obtained from the corresponding phosphates, although with poor efficiency.